Tempestuous - Askew, Kim.; Helmes, Amy. (Blue Ash, Ohio : Merit Press, 2012)
Miranda has been ousted from the popular girls' group at school, and she finds a way to get revenge by teaming up with some geeks at the local mall.
"F+W Media Inc."
Keywords: Revenge -- Juvenile fiction; High school students -- Juvenile fiction; Cliques (Sociology) -- Juvenile fiction; Revenge -- Fiction; High school students -- Fiction; Cliques (Sociology) -- Fiction